Residents' evaluation of community center revitalization with murals: Aesthetics, local identity, and ownership - Setyawan, Siti Luzviminda Harum Pratiwi; Sutarto, Sutarto; Putri, Marinda Noor Fajrina Noviana; Purwanto, Danang; Syakur, Muhammad Yusron; Mukhrodin, Muhammad Fadil Hidayatulloh (Nur Science Institute, 2025)
A mural project was implemented as a visual enhancement for the community center. This study examines residents' perspectives on mural interventions and evaluates the effectiveness of measurement tools. The mural project took one month to complete, but preparation, including discussions with the community head, also required one month. Post-project surveys were gathered online via a Likert scale, employing a quantitative descriptive method. Item validity and internal reliability were assessed using item-total correlations and Cronbach's alpha. Twenty respondents participated in the survey. The instrument demonstrated strong reliability (α = 0.78) with 14 valid items. The findings indicate that the average perception across dimensions falls within the mid-range, with social interaction leading at 58.20%, followed by sense of ownership at 55.60%, revitalization evaluation at 55.32%, aesthetic perception at 55.00%, local identity at 54.60%, and community pride at 53.20%, which is the lowest. The findings indicate that murals effectively stimulate social interaction, though they have not yet fully realized their potential to build community pride. Practical implications involve enhancing theme curation rooted in local identity, engaging residents in maintenance, and creating regular activity programs to boost pride.